INFLUENCE OF ROW SPACING ON PLANT PRODUCTIVITY OF MODERN WINTER RYE HYBRIDS (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2026)
The article presents the results of a three-year study on the effect of row spacing (12.5, 15.0, and 19.0 cm) on the productivity of modern winter rye hybrids (hybs.) ‘Tayo’ and ‘Trebiano’.Problem Articulation. The average yield of winter rye in Ukraine is 2.4 t/ha, reaching up to 6.0 t/ha in leading farms, while the world record stands at 11.8 t/ha. The primary cause of low winter rye yields is violations of cultivation technologies. Optimal nutrition area, which is determined by appropriate row spacing selected during sowing, is a key factor influencing plant productivity is the. Currently, the Ukrainian market is saturated with state-of-the-art seed planters from both domestic and leading global manufacturers. In this regard, the purpose of our study was to determine the optimal row spacing for modern winter rye hybrids using various seed planters that differ in row width and sowing mechanism design. Methods. The study was conducted at the Mykolaivskyi Agricultural Complex in the Koriukivka district of the Chernihiv region in 2022-2024. Two modern foreign winter rye hybrids, ‘Tayo’ and ‘Trebiano’ (included in the State Register of Plant Varieties in 2021 and 2020, respectively; originator – KWS, Germany), were selected for the study. The experimental variants included the following row spacings: 1) 12.5 cm (sown with a Kverneland u-drill); 2) 15.0 cm (sown with an Astra Nova seed planter); 3) 19.0 cm (sown with a Great Plains NTA3510 seed planter). To achieve the research objectives, a two-factor field experiment was laid out using a systematic plot arrangement in three replications, following standard methodologies. Results. The tillering capacity coefficient was higher at a row spacing of 12.5 cm for both winter rye hybrids. Under the influence of the studied row widths, it ranged from 2.4 to 3.8 in hyb. ‘Tayo’ and 2.2 to 3.5 in hyb. ‘Trebiano’. Slightly taller plants were observed in both hybrids at a row spacing of 19.0 cm. This seems logical, as narrowing the distance between plants within a row due to wider row spacing increases inter-plant competition, causing them to elongate. On average across the study years, the maximum plant height (133.2 cm) was recorded in winter rye hyb. ‘Trebiano’. The longest spike (12.2 cm) was formed by winter rye hyb. ‘Trebiano’ at a row spacing of 19.0 cm, and it was 0.7 and 0.9 cm longer than at 15.0 and 12.5 cm spacings, respectively. Hyb. ‘Tayo’ formed the greatest number of productive stems (530 stems/m²), which was 35 stems/m² more than hyb. ‘Trebiano’; we think that this difference can be attributed to specific hybrids’ characteristics. Grain weight per spike was higher at a row spacing of 12.5 cm in both hybrids. In the experiments on hyb. ‘Trebiano’, it amounted to 1.64 g, while in hyb ‘Tayo’, it was 0.23 g lower. Widening the row spacing led to a decrease in grain weight per spike by 0.03–0.07 g for both winter rye hybrids. The thousand-kernel weight (TKW) in hybs. ‘Tayo’ and ‘Trebiano’ was higher by 0.60–1.40 g and 0.80–1.60 g, respectively, when they were sown at a 12.5 cm row spacing. With wider row spacing, the TKW decreased by 0.70–1.50 g in both winter rye hybrids. The highest grain yields – 8.26 t/ha from hyb. ‘Tayo’ and 8.71 t/ha from hyb. ‘Trebiano’ – were harvested when the hybrids were sown at a row spacing of 12.5 cm. Widening the row spacing to 15.0 cm reduced yields by 1.10 t/ha in hyb. ‘Tayo’ and 0.68 t/ha in hyb. ‘Trebiano’. Further widening to 19.0 cm resulted in an even greater yield reduction of 1.81 and 1.59 t/ha, respectively. Conclusions. Thus, to ensure higher grain productivity of both studied winter rye hybrids, it is advisable to sow them at a 12.5 cm row spacing.
Keywords: winter rye; hybrids; row spacing; linear plant parameters; yield components; yield